"Dialectics of soul" and other psychological techniques in the novel "The Last Day" by Mikhail Naimy - Vlasova, Yulia Evgenievna; Vavichkina, Tatiana Anatolevna (Филология: научные исследования, 2024)
The object of the study is the novel "The Last Day" by the Lebanese writer Mikhail Naimy. The subject of the study was the "dialectic of the soul" and "stream of consciousness", that is, techniques for describing the human condition borrowed from Leo Tolstoy masterpieces. For one day, the soul of Musa al-Askari overcomes severe suffering, it dies and is reborn in a new form. A small person turns into a strong personality. Psychological techniques for describing borderline human states, taken from Fyodor Dostoevsky, also helped the Lebanese writer to reveal the depths of the hero's personality. The scientific novelty of the article is that the Russian writers' techniques are found in the little-studied Arabic novel "The Last Day" that is an illustration of the Russian literature influence on Arab culture. For the first time in Russian literary study, this novel is analyzed from the "dialectic of the soul" perspective. The research was conducted on the basis of historical, literary, comparative methods, using scientific methods of observation and description, analysis and synthesis. As a result, it is noted that the novel narrative is organized according to the psychological realism, in which there is a psychological analysis passed through the stream of consciousness, an internal monologue and the dialectic of the soul. The authors conclude that Naimy took a humanistic approach and a special psychological manner of narration from Russian literature, including Tolstoy and Dostoevsky's works, to convincingly prove that a person is a fine–tuned mechanism, that kindness will save the world, and the secret of happiness lies in serving people. The practical significance of the research is that its results develop the topic of cultural ties between Lebanon and Russia. The article contributes to the development of Arabic literature, which remains poorly studied by Russian literary study.